2011
DOI: 10.1002/chem.201002707
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Size Effects in Lewis Base Induced Reductions in Organolanthanide Chemistry

Abstract: The reaction of the tripodal 1,3,5-trialkyl-1,3,5-triazacyclohexanes (L=cyclo-[N(R)CH(2)](3) , R=Et, iPr, tBu), with [Sm(AlMe(4))(3)] resulted in the formation of divalent samarium complexes of the constitution [{L(n)Sm(AlMe(4))(2)}(m)] (n, m=1,2) under ethane extrusion. These compounds were characterised by single-crystal X-ray diffraction and elemental analyses. Simultaneous occurrence of Lewis base induced reduction and C--activation reactions is observed. The ratio of products depends on the bulkiness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(25 reference statements)
1
19
0
2
Order By: Relevance
“…[13] The angle enclosed by the two nitrogen atom planes of the ligands (46.08) is comparable to that of the divalent samarium compounds [(TiPTAC) 2 SmA C H T U N G T R E N N U N G (AlMe 4 ) 2 ] (47.58) [21] and results in a compressed…”
Section: Resultsmentioning
confidence: 89%
“…[13] The angle enclosed by the two nitrogen atom planes of the ligands (46.08) is comparable to that of the divalent samarium compounds [(TiPTAC) 2 SmA C H T U N G T R E N N U N G (AlMe 4 ) 2 ] (47.58) [21] and results in a compressed…”
Section: Resultsmentioning
confidence: 89%
“…The triazacyclohexane derivatives were prepared according to our earlier reports. [15][16][17][18] [La(AlMe 4 ) 3 ] and [Pr(AlMe 4 ) 3 ] were synthesised by a literature method. [12] NMR measurements were recorded with Bruker DRX 500 and Avance 600 spectrometers.…”
Section: Methodsmentioning
confidence: 99%
“…Closer investigation of this reaction with variation of R showed that the isomeric tris(aluminate) ion with two methylidene units had formed in C-H activation reactions besides BIR, namely [(TiPrTAC)La(AlMe 4 )({μ 3 -CH 2 }{AlMe 2 (μ 2 -Me)} 2 )] in the case of R = iPr. [17] A third type of reaction between Ln(AlMe 4 ) 3 and TRTAC ligands was observed for the combinations Ln = Y and R = Cy: in this case the formation of methyl cations of the formula [(TCyTAC) 2 YMe 2 ]…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[23,24] Bei der Reaktion von [La{Al(CH 3 ) 4 } 3 ] mit TiPTAC wurden keine weiteren Produkte erhalten, [23] wogegen bei der Reaktion von [Sm{Al-(CH 3 ) 4 } 3 ] mit TiPTAC [(TiPTAC)Sm{Al(CH 3 ) 4 }{m 2 -Al-(CH 3 ) 4 }] 2 (16) als weiteres Produkt gebildet wird (Schema 10). [24] In den Verbindungen 15 betragen die Ln-CH 2 -Abstände 2.542(4) und 2.521 (4) [25] Die Reaktionen von [Ln{Al(CH 3 ) 4 } 3 ] (Ln = Y, Sm) mit anderen 1,3,5-Trialkyl-1,3,5-triazacyclohexanen (Alkyl = Ethyl, tert-Butyl, Cyclohexyl) führten nicht zur Bildung von Methylidenkomplexen. [24][25][26] .…”
Section: Angewandte Chemieunclassified